Metabolites in Modern Medicine: Decoding the Future of Health and Diseases - B. Harshitha; Ashwini V; Fazeela Mahaboob Begum S.M (Emerging Trends in Metabolites, 2024)
The end products of many metabolic processes in cells are called metabolites. Each reaction contributes a specific metabolite. Metabolites act as fingerprints of on-going biological processes. Constant changes in cellular composition due to both environmental and internal factors. By analysing the types and presence of metabolites, scientists can effectively reconstruct the inner workings of a cell or organism. In the past, analysing metabolites was a slow and tedious process, often limited to measuring a small number of known metabolites. As technology advances, the development of new analytical tools has made metabolic profiling convenient by screening thousands of metabolites simultaneously. By analysing changes in metabolite profiles, we can identify the effects of environmental contaminants on organisms. As the downstream products of gene expression and environmental interactions, metabolites serve as valuable biomarkers for various diseases. With their ability to predict treatment response, diagnose diseases earlier, and improve patient outcomes, metabolite biomarkers hold great promise to revolutionize the healthcare profession. By identifying unique metabolic fingerprints researchers can stratify patients into subgroups with distinct disease trajectories and treatment responses. Metabolomics is being used to develop personalized therapies that will improve patient outcomes and reduce side effects. Advances in technology of metabolomics paves a way for its integration into the clinical practices. This promises a future where diseases can be prevented, diagnosed, and treated, leading to improved health and longevity. This review highlights the metabolome’s significance as a tool for understanding cellular function and disease. It also explores the application of metabolomics in various fields of biology and medicine.
Keywords: Biomarkers; Metabolites; cellular function; disease; environmental contaminants; metabolic profile